Subsurface structural maps over the Central North American rift system (CNARS), central Kansas, with discussion - Berendsen, Pieter; Blair, Kevin P. (Bulletin (Kansas Geological Survey), 1986)
Contour maps upon multiple horizons within a 125 by 60 mi (190 by 90 km) area of central Kansas reveal that the present-day structural configuration has resulted from repeated reactivation of Precambrian trends. Three major tectonic trends are defined. The Nemaha and Peace Creek tectonic zones identify the Paleozoic reactivated margins of the northeast-southwest-trending Keweenawan Central North American rift system (CNARS). The northwest-southeast-trending Fall River tectonic zone (FRITZ) parallels the Churchill accretionary terrane boundary. Structures were subjected to repeated movement during the Paleozoic, culminating with the Pennsylvanian Ouachita orogeny. Vertical tectonism involving a substantial component of strike-slip motion played an important role in the formation of observed structures.